2008
DOI: 10.1136/bjo.2007.117812
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vernal keratoconjunctivitis: a rare disease?

Abstract: Based on the most likely hypotheses concerning disease duration and non-responding ophthalmologists' VKC case rate, the best estimate of VKC prevalence in Western Europe is 3.2/10,000 inhabitants. The prevalence of VKC with corneal complications is 0.8/10,000 inhabitants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 25 publications
3
67
0
4
Order By: Relevance
“…It is unusual in most of North America and Western Europe. 19 A study conducted in school children of Karachi by Baig R et al in 2010 showed a prevalence of allergic conjunctivitis of 19.2 % which is close to the findings of this study (20.9%).…”
supporting
confidence: 89%
“…It is unusual in most of North America and Western Europe. 19 A study conducted in school children of Karachi by Baig R et al in 2010 showed a prevalence of allergic conjunctivitis of 19.2 % which is close to the findings of this study (20.9%).…”
supporting
confidence: 89%
“…However, it is not unusual to see occasional vernal conjunctivitis patients throughout the United States and Canada. The prevalence of VKC in Europe ranges from 1.2 to 10.6 cases per 10,000 population, although the prevalence of associated corneal complications is much lower (0.3-2.3 per 10,000 population) [15]. Young people are typically affected [16].…”
Section: Allergic Conjunctivitismentioning
confidence: 99%
“…The prevalence of VKC varies greatly and increases with vicinity to the equator. In Scandinavian countries, prevalence is close to 0%, whereas it reaches 0.27% in Italy and is higher still in Africa, with a reported prevalence of 6% in Ethiopia . Although the causes of VKC are still unclear, there is a strong correlation with exposure to sunlight, which exacerbates the disease …”
Section: Introductionmentioning
confidence: 99%